Alterations of the Oestrous Cycle and Increase in the Blood Pressure in Normotensive Female Rats by Continuous Exposure to Light - Martinez-Salinas, J; Rios-Ramirez, M; Jaimes-Fernandez, L (University of Agriculture, 2023)
The study aims to investigate changes on some cardiac parameters of normotensive female rats due to continual exposure to light. Three months old female Wistar rats were subjected to varying light cycles and intensities, following which cardiovascular parameters were recorded continuously at days 0, 10, 15, 20, 25 and 30. We calculated and recorded the mean arterial pressure, pulse pressure, peripheral resistance and cardiac output. It was observed that continuous exposure to light for 10 days significantly increased the mean arterial pressure (MAP; 103±1 mmHg control vs. 117±6 mmHg at 20 min; P<0.05) and the systolic blood pressure (SBP; 111±1 mmHg control vs. 130±5 mmHg at 20 min; P<0.05). Heart rate (HR) did not significantly change during the exposure to light. However, the pulse pressure (PP) increased at day 20 on exposure to light (18±1 mmHg control vs. 32±4 mmHg at 20 min; P<0.05). It also reduced the peripheral resistance, while increasing the cardiac output in the female rats. It also elevated oestrogen plasma levels and LF/HF ratio, which is a spectral component of ECG denoting heart rate variability (HRV). Continuous exposure to light may induce stress in female rats, leading to hormonal blood pressure, and sympathovagal imbalances. © 2023 University of Agriculture. All rights reserved.